A contrastive analysis of English perspective modals of necessity, certainty and ability and their Vietnamese equivalents from systemic functional perspective = So sánh đối chiếu các trợ động từ tình thái hoàn thành tiếng Anh biểu hiện sự cần thiết, sự ch - Nguyễn, Thị Liên (ĐHNN, 2017)
47 p. + CD-ROM